Rapid solution combustion synthesis of novel superfine CaLaAl1-xCrxO4 red ceramic pigments. Issue 2 (15th January 2022) - Zhou, Wenwu; Chen, Long; Zhuo, Sheng; Peng, Rong; Yu, Danxia; Fang, Ping; Liu, Yue; Chen, Weifan
Abstract: Superfine CaLaAl1-x Crx O4 (x = 0.02, 0.05, 0.08, 0.10) red ceramic pigments have been prepared by solution combustion reaction and subsequent high-temperature calcination. All of the pigments were characterized by X-ray diffraction (XRD), Field scanning electron microscopy (FESEM), UV–Vis spectrophotometry, Laser particle size analyzer and CIE L*a*b* spectrophotometry. Moreover, the effects of the doping amount of Cr 3+ ion, calcination temperature, salt assistance and synthetic routes on chromatic performance and particle size distributions of the pigments were also investigated. The results showed that CaLaAl1-x Crx O4 pigment particles prepared via solution combustion reaction and subsequent calcination were well-dispersed and uniform in size. With the increase of doping amount of Cr 3+ ion, the brightness value L* of CaLaAl1-x Crx O4 pigments decreased obviously and the redness value a* increased gradually. When x = 0.08, it showed the best chromatic performance (L* = 39.37, a* = 21.33, b* = 13.99). In addition, the synthetic pigments possess excellent high temperature stability which is conducive to the application of ceramic pigments. Most importantly, the synthetic method of CaLaAl1-x Crx O4 red ceramic pigments is not only cheap in raw materials, but also easy to industrialize.